2019
DOI: 10.1021/acsnano.8b07401
|View full text |Cite
|
Sign up to set email alerts
|

Customizing Morphology, Size, and Response Kinetics of Matrix Metalloproteinase-Responsive Nanostructures by Systematic Peptide Design

Abstract: Over-expression and activation of matrix metalloproteinase-9 (MMP-9) is associated with multiple diseases, and can serve as a stimulus to activate nanomaterials for sensing and controlled release. In order to achieve autonomous therapeutics with improved space-time targeting capabilities, several features need to be considered beyond the introduction of an enzyme-cleavable linker into a nanostructure. We introduce guiding principles for a customizable platform using supramolecular peptide nanostructures with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 60 publications
3
84
0
Order By: Relevance
“…in close proximity of cancer cells. 2,6,[12][13][14][15][16][17][18][19][20] Several studies suggested a mechanism that involves an initial internalization of the precursor by the cells, followed by intracellular enzymatic transformation and assembly that leads to cellular death. 6,18,21 Most of the described precursors are based on short self-assembling peptides that are functionalized with enzymatic sensitive moieties.…”
Section: Introductionmentioning
confidence: 99%
“…in close proximity of cancer cells. 2,6,[12][13][14][15][16][17][18][19][20] Several studies suggested a mechanism that involves an initial internalization of the precursor by the cells, followed by intracellular enzymatic transformation and assembly that leads to cellular death. 6,18,21 Most of the described precursors are based on short self-assembling peptides that are functionalized with enzymatic sensitive moieties.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Recently, Ulijn and coworkers reported a peptide design approach to tune the degradation kinetics of supramolecular peptide nanostructures by MMP-9. 25 Peptides were designed with systematically modified amino acid sequences to control overall charge and order in the MMP-9 substrate region. As result of this systematic design, nanostructures with different secondary structures and morphologies (nanofibers, elongated worm-like micelles and spherical micelles) were formed by self-assembly, not being possible to isolate the effect of nanostructure morphology on MMP cleavability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, guiding principles to customize the kinetics and morphological changes in supramolecular peptide nanostructures have been introduced by Son et al (2019) upon exposure of matrix metalloproteinase. These guiding principles enumerate systematic customization of enzyme-responsive peptide nanostructures by exchange of just a few amino acids, for general use in performance optimization of enzymeresponsive materials (Son et al, 2019). The advantages of enzyme-instructed self-assembly (EISA) in triggering the molecular self-assembly in situ, by overexpression, to prepare supramolecular biofunctional materials and hydrogels has been reviewed by Gao et al (2019).…”
Section: Impact Of Chemical Modificationsmentioning
confidence: 99%